Thermal management of photovoltaics with thermal energy storage units filled with microencapsulated PCMs - Soares, N. (2017)
High operating temperatures reduce the performance of photovoltaic (PV) devices by reducing the efficiency of solar to electrical energy conversion in the PV cells. This paper presents a numerical study based on the effective heat capacity method to evaluate the thermal performance of a PV system incorporating a thermal energy storage unit filled with a microencapsulated phase change material (PCM) – Micronal® DS 5001 X. The PCM module is intended to control the temperature rise in the PV cells. The main goal of this work is to find the ideal thickness of the PCM module for the climatic conditions of Coimbra, Portugal, and to evaluate how the thermal regulation potential of PCMs (during phase change) can be used to improve the performance of the PCM-enhanced system (PV/PCM). By comparing the temperature time evolutions in the cells of the PV/PCM and the conventional PV systems, an effective thermal regulation of the PV/PCM system was observed from 6am to 3pm. Therefore, it is concluded that TES units filled with microencapsulated PCMs can be used to improve the energy performance of PV systems by reducing high operating temperatures due to solar irradiation. It was also concluded that, for the studied conditions, the ideal thickness of the PCM module was about 3.3 cm, thus increasing the energy performance of the system up to 0.8%.